Tantangan Regulasi Kecerdasan Buatan (AI) dalam Perspektif Hukum Perlindungan Data Pribadi di Indonesia - Kimmy Baby Kirana; Wilma Silalahi (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Advances in artificial intelligence (AI) technology have had a wide and significant impact on various sectors of life, ranging from public services, finance, health, education, to law enforcement. These technologies enable process automation, service efficiency, and fast, data-driven decision-making. However, behind its benefits, the use of AI brings serious challenges to the protection of the right to privacy and personal data. AI works by collecting, processing, and analyzing data at scale, including personal and sensitive data, thereby creating a risk of abuse and violation of the fundamental rights of individuals. In Indonesia, even though Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) has been passed as an important milestone in the protection of digital rights, its application and regulation of the use of AI is still not comprehensive and detailed. Existing regulations do not explicitly regulate the principles of algorithm transparency, supervision of the decision-making automation process, and legal accountability mechanisms in the event of losses due to AI system decisions. Therefore, this article aims to analyze these regulatory challenges through a normative juridical approach based on legislative studies and academic literature in order to provide constructive recommendations for strengthening personal data protection in the era of artificial intelligence.